Genomic organization of the ATM gene - Uziel, Tamar; Savitsky, Kinneret; Platzer, Matthias; Ziv, Yael; Helbitz, Tal; Nehls, Michael; Boehm, Thomas; Rosenthal, Andre; Shiloh, Yosef; Rotman, Galit (Genomics, 1996)
The ATM gene was recently identified and found to be responsible for the human genetic disorder ataxia-telangiectasia. The major ATM transcript is 13 kb. Using long-distance PCR, we determined the genomic structure of this gene and identified all of its exon-intron boundaries. The ATM gene spans approximately 150 kb of genomic DNA and consists of 66 exons. The initiation codon falls within exon 4. The last exon is 3.8 kb and contains the stop codon and a 3′-untranslated region of about 3600 nucleotides.